2011
DOI: 10.2466/22.24.27.pms.113.5.425-430
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity and P300 to Behaviorally Perceptible and Imperceptible Frequency and Intensity Contrasts

Abstract: Mismatch negativity and the P300 have been investigated as electrophysiological indices of behavioral auditory discrimination of duration. Using an oddball paradigm, responses were evoked to stimuli that had been behaviorally demonstrated to be either perceptible or imperceptible. The results indicated P300 events were present with the perceptible contrast but absent for the imperceptible contrast with all participants, while mismatch negativities were present in approximately 80 and 20% of participants to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…MMN ¼ mismatch negativity; SWC ¼ stressed word condition; UWC ¼ unstressed word condition. White & Stuart, 2011). In addition, the longer word durations of stressed words in this study might have played an important role in eliciting larger MMNs.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…MMN ¼ mismatch negativity; SWC ¼ stressed word condition; UWC ¼ unstressed word condition. White & Stuart, 2011). In addition, the longer word durations of stressed words in this study might have played an important role in eliciting larger MMNs.…”
Section: Discussionmentioning
confidence: 71%
“…This study revealed that MMN amplitude was larger in the SWC than in the UWC. These data implied that it was the frequency and intensity (spectral) contrast of the SWC that accounted for this finding (Stoody et al., 2011; White & Stuart, 2011). In addition, the longer word durations of stressed words in this study might have played an important role in eliciting larger MMNs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The MMN can be affected by numerous variables, including stimulus parameters and participant factors. Stimulus parameters include intensity [3,17,18], frequency [18,19,20],…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Further, for probing perceptual processes related to auditory information, some studies have investigated attention allocation in the auditory modality—this is typically done by varying salient sound features such as intensity, complexity, or even emotional valence (Alho et al, ; Meinhardt & Pekrun, ; White & Stuart, ). The P300, a positive deflection peaking at around 300 ms after the onset of rare salient events in a stimulus sequence, has been described as an index of the auditory attention function (Grossi & Coch, ; Polich, ).…”
Section: Introductionmentioning
confidence: 99%